Examining the Trends of Published Literature on Post Occupancy Evaluation (POE): A Bibliometric Analysis - Mustaffa, Wan Nor Faezah Wan; Ani, Adi Irfan Che; Hussain, Afifuddin Husairi Mat Jusoh; Alias, Rusnani; Nordin, Mohd Norazmi; Hussain, Mashitah Mohd (CENTRAL ASIA AND THE CAUCASUS, 2022)
The Post-Occupancy Assessment Research (POE) program was initiated in 1979. Since then, researchers have frequently used the term POE to investigate POE in the relevant industry further. Therefore, this study aims to analyze and examine the titles of papers and articles from the Scopus Post-Occupancy Evaluation database. Various tools, including Microsoft Excel, were used for frequency analysis and Wordsift for text visualization. The standard bibliometric methodology was used to show the growth of publications and research production. Based on the search results, a total of 381 doc- uments were retrieved. The growth rate of literature on post-occupancy evaluation has increased year by year since 1979. Most of the publications, particularly those written in English, have been published in journals and conferences. Engineers carried out the majority of the post-occupancy assessments. The majority of the terminology used in the post-occupancy evaluation represents the key research fields. The majority of POE-related research has taken place in the United States. This study presents the evolution of the POE scientific literature and identifies areas of current research interest and future research directions.